Potential of Bacillus subtilis PB6 in corn-based diets to combat subclinical necrotic enteritis in broilers - Most Khairunnesa; Alip Kumar; Kosar Gharib-Naseri; Mingan Choct; Reza Barekatain; Shu-Biao Wu (Poultry Science)
Bacillus-based probiotics and dietary enzymes have gained attention for supporting gut health, nutrient digestion, and intestinal integrity in poultry. This study evaluated the effects of Bacillus subtilis PB6 (Pb) and xylanase (Xy), individually and in combination, on the performance, intestinal lesions, and histomorphology of broiler chickens challenged with subclinical necrotic enteritis (SNE). A total of 630-d-old, mixed-sex Cobb 500 broilers were utilized in a 2 × 2 + 1 factorial arrangement of treatments: NE challenge without additives (CC); NE challenge with Xy at 0.03 % (Xy); NE challenge with Pb at 0.05 % (Pb); NE challenge with Xy at 0.03 % and Pb at 0.05 % (Xy+Pb); and, a non-challenge, additive free control (NC). In the pre-challenge period, birds in NC and CC groups were considered a control. A significant Xy × Pb interaction was observed for body weight gain (BWG) (P < 0.01) and FCR (P < 0.05) before challenge (d0-8). Pb efficacy for reducing FCR was significant without Xy supplementation, while Xy enhanced BWG without Pb (P < 0.01). During d9-19, all challenged birds showed reduced BWG (P < 0.05) and increased FCR (P < 0.05) compared to NC birds. During d20-35 and d0-35, Pb significantly improved FCR and reduced feed intake (FI) as the main effect among challenged birds (P < 0.05), equating the performance of NC birds (P > 0.05). NE challenge increased (P < 0.05) duodenal lesions in females but not males. A significant Xy × Pb interaction (P < 0.05) was observed for villus height (VH) and the VH to crypt depth (CD) ratio. Pb enhanced VH and VH/CD (P < 0.05) only when Xy was not supplemented. Furthermore, Pb-fed birds showed a trend towards increased villus surface area (VSA) (P = 0.067). In conclusion, Pb improves feed efficiency and mitigates the adverse effects of SNE-induced damage to intestinal health, while Xy enhances pre-challenge growth without augmenting Pb’s benefits during NE.